Localization of mental and mandibular foramens on the conventional and digital panoramic images - Peker, Ilkay (Array, 2009)
Abstract: The purpose of this study was to compare the efficiency of conventional and digital panoramic images for localization of mental and mandibular foramens. Six dry edentulous human mandibles were used in the study. Conventional and digital panoramic images were obtained and the vertical and horizontal measurements were performed for localization of mental and mandibular foramens on the images. The correlations between radiographic (conventional and digital) and direct measurements were compared. A measurement error between the radiographic and direct measurements was determined at the level of 1 mm. The measurement errors were generally less in conventional panoramic radiography than digital one. There was statistically strong positive correlation between direct and radiographic measurements. Statistically significant difference was found between radiographic and direct measurements for bone height of mandible in ramus region. According to the results of this study, diagnostic performance of conventional and digital panoramic images seems to be equal for the localization of mental and mandibular foramens. The vertical radiographic measurements are generally reliable and correlated with direct measurements in mandible for conventional and digital panoramic radiography, but the evaluation of bone height in ramus region may not be sufficiently reliable